DELSILIFE in the Philippines [videorecording] an educational strategy to fight poverty - Boeren, Ad JJM (CESO-INNOTECH, 1988)
DELSILIFE is a development project aimed towards alleviating poverty through education. The documentary focuses on Loma de Bato, Bulacan and Jehnoc, Iloilo - two communities which have been helped by the DELSILIFE learning program. DELSILIFE offers two major types of programs: The Livelihood Learning Program; and the Basic Life Skills program. The DELSILIFE education not only equipts the community members with skills but has also improved their attitudes.